Evaluasi Peningkatan Kualitas Ruang Terbuka Hijau Kota dengan Indeks Hijau Biru Indonesia di Kota Bandar Lampung - Ali, Muhammad Saddam; Hutriani, Ina Winiastuti; Idris, Anis Wirda; Amanda, Zulvita; Hetharia, Bartholomew Jordan; Wistoro, Luthfie Adli (Jurnal Lanskap Indonesia, 2025)
Bandar Lampung is one of the major cities on the island of Sumatra that seeks to fulfill the availability of Green Open Space (GOS). Based on 2024 statistical data, Bandar Lampung only has 601.08 ha of GOS (3.05% of the total city area), so Bandar Lampung still needs 26.95% of GOS target to fulfill the 30% GOS target as mandated by Law No. 26 of 2007 concerning Spatial Planning. The innovative paradigm of GOS has been adapted by the Regulation of the Minister of ATR / BPN Number 14 of 2022 concerning the Provision and Utilization of Green Open Space, that GOS does not only consist of green space but also non-green open space (NGOS) and blue open space (BOS) through GOS typology and fulfillment of quantity and quality through the Indonesia Green-Blue Index (IGBI). The purpose of this research is to evaluate the green space of Bandar Lampung City using IGBI to maximize the available urban space in fulfilling the availability of quantity and quality of green space. This research went through three main stages, i.e., (1) qualitative data collection of related regulations and policies; (2) spatial analysis of the city's Regional Spatial Plan map; and (3) synthesis in the form of GOS typology classification then calculating the quantity and quality of GOS using IGBI. Based on the results of the analysis of the spatial pattern plan map of the Bandar Lampung City Spatial Plan 2021-2041, it is known that there are four main typologies of green spaces in Bandar Lampung. The results of the calculation of the quantity and quality of GOS with IGBI obtained the area of GOS in the spatial pattern plan is equivalent to 8,400.13 m2 or equivalent to 46% of the entire area of Bandar Lampung. Improving the quality of GOS to suit its typology can be done by fulfilling the minimum area of green cover, completeness of vegetation stratification, recommended non-green cover, BOS, and several facilities as required by its typology.